QUALITATIVE ASPECTS CONCERNING CERTAIN MINCED MEAT PRODUCTS FROM ROMANIAN MARKET - Radiana-Maria TAMBA-BEREHOIU; Luminiţa VIŞAN; Mira TURTOI; Vasilica SIMION; Ciprian Nicolae POPA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper aimed to analyze the quality of some minced meat assortments, namely: pork minced meat, beef minced meat, pork-beef minced meat mixture and traditional sausages paste, which are often sold on the Romanian market. Moisture (%), fat (%), easily hydrolysable nitrogen (NH3), total nitrogen (% protein), collagen content (%) and the C/P (collagen/protein) ratio were analyzed during experiments. Differences with varying degrees of significance were identified between quality parameters of minced meat assortments (Student test). Significant differences were found between the samples of minced meat and traditional sausages paste, regarding humidity (%), fat (%), easily hydrolysable nitrogen (NH3) and total nitrogen (protein%).Traditional sausages paste has significantly elevated values of fat (%) and easily hydrolysable nitrogen (%) when compared with pork minced meat (3.369**, 16.010***), beef minced meat (9.255***, 16.979***) and pork-beef minced meat mixture (7.277***, 17.364***); instead, it has the lowest protein content when compared with pork minced meat (6.677***), beef minced meat (13.174***) and pork-beef minced meat mixture (5.983***). We find that all the formed significant correlations have particularized minced meat assortments, because of the fact that some of the assortments did not show significant correlations between the same quality parameters, for example in the pork – beef minced meat mixture, where fat correlated to collagen (r = -0.621*) and to C/P ratio (r = 0.731**), easily hydrolyzable nitrogen (NH3) correlated to C/P ratio (r = 0.538*) and also protein correlated to collagen (r = 0.604*). All observed correlations, with varying degrees of significance, constituted peculiarities of minced meat assortments taken for analysis.